Sex differentiation and risk factor evaluation in stroke patients - Bhattacharjee, M; Ahmed, S; Rahman, KM; Uddin, MJ; Dey, SK; Israil, A; Mondal, G; Miah, AH; Roy, GC (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):371-376 The abstract of this article is available on the PubMed website